bonsoir,
A = 81x² + 144x +64
B = 36 - 60x +25x² ⇒ B= 25x² - 60x +36
C = 16x² - 49
D = x² + 2x +1 +4x² - 25 ⇒ D = 5x² +2x - 24
E = x² - 4 - 3( 2x² -8x +16) + (10x + 15 ) ( 1 - 7x)
E = x² - 4 - 6x² + 24x - 48 + 10x - 70x +15 - 105x
E = - 4x² - 140x - 37
exercice 2
F= x² + x + 2x +2 - 5x - 5
F = x² - 2x - 3 ⇒ F = x(x-2) - 3
G = ( 6x - 5 )²
H = 3 (x² -5)
I = ( 8x + 9 )²
J = ( 4 - 7x)²
exercice 3
1/4 x - 3 = 6
1/4 x = 6 + 3
x = 9 ÷ 1/4
x = 9x4
x = 36
3x - 2x = 12 + 7
x = 19
- 9x - 6 = -6x -3x - 6
- 9x + 6x + 3x = - 6 + 6
-0x = 0
x = 0